43.6k views
3 votes
Use the remainder theorem to find P(3) for P(x) = 2x° -6x²-8.Specifically, give the quotient and the remainder for the associated division and the value of P (3).금QuotientXХ5?Remainderp(3) - I

Use the remainder theorem to find P(3) for P(x) = 2x° -6x²-8.Specifically, give the-example-1
User Csgeek
by
5.1k points

1 Answer

5 votes
Answer:
\begin{gathered} Quotient\text{ = 2x}^2 \\ Remainder\text{ = -8} \\ P(3)\text{ = -8} \end{gathered}

Step-by-step explanation:
\begin{gathered} Given\text{ polynomial:} \\ P(x)\text{ = 2x}^3\text{ - 6x}^2\text{ - 8} \\ We\text{ need to apply the remainder theorem to get the quotient and remainder} \end{gathered}

P(3): To apply the remainder theorem, we will substitute the value of x with 3 in the function


\begin{gathered} P(3)\text{ = 2\lparen3\rparen}^3\text{ - 6\lparen3\rparen}^2\text{ - 8} \\ P(3)\text{ = 54 - 54 - 8} \\ P(3)\text{ = -8} \end{gathered}
\begin{gathered} The\text{ remainder is value left after substituting the value for x} \\ The\text{ remainder = -8} \end{gathered}

To get the quotient, we will apply long division:


\begin{gathered} From\text{ }P(3),\text{ x = 3} \\ \text{ gives a factor of \lparen x - 3\rparen} \\ (2x^3-6x^2-8)/((x-3)) \end{gathered}
\begin{gathered} Quotient\text{ = 2x}^2 \\ Remainder\text{ = -8} \\ P(3)\text{ = -8} \end{gathered}

Use the remainder theorem to find P(3) for P(x) = 2x° -6x²-8.Specifically, give the-example-1
User Johann Dirdal
by
4.6k points